Employer-provided vocational training in Europe : evaluation and interpretation of the third continuing vocational training survey - (:unkn) unknown (Publications Office of the European Union, 2010)
This report provides the first European detailed comparative analysis of the results of the third European continuing vocational training survey (CVTS3). "Radar charts are used to assess national CVT performance in incidence, participation, intensity and expenditure. The analysis reveals that other forms of training in enterprises complements rather than competes with the more traditional courses. The concern about enterprises not providing training is substantiated from a social and economic perspective. In-depth analysis of CVTS3 data shows that professional management of training, involvement of social partners and targeted public measures are crucial to fostering training. It also shows gaps in enterprises’ perception of skills and training needs. As most enterprises do not change their training behaviour over time, triggering non-trainers to provide training remains a challenge. Generally, policy measures to lower training costs remain of minor relevance to enterprises. Therefore, European and national policies should develop targeted financial instruments. The report ends with a detailed quality evaluation of CVTS3 from the European perspective and gives various recommendations to improve the quality of the survey." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; T 3.4 Befragung; T 1.5 International vergleichende Berufsbildungsforschung; Betriebliche Weiterbildung; Betriebsbefragung; CVTS; Weiterbildungsbeteiligung; Qualitätssicherung; Internationaler Vergleich; Benchmarking